2019
DOI: 10.1177/1724600819866456
|View full text |Cite
|
Sign up to set email alerts
|

miR-142-3p as a novel biomarker for predicting poor prognosis in renal cell carcinoma patients after surgery

Abstract: Background: miR-142-3p has proved to be involved in tumorigenesis and the development of renal cell carcinoma. The present study aimed to explore the prognostic value of miR-142-3p. Methods: Total RNA was extracted from renal cell carcinoma specimens and the expression level of miR-142-3p was measured. Pearson Chi-square test, Kaplan–Meier analysis, as well as univariate and multivariate regression analysis were performed to determine the correlation between miR-142-3p and the prognosis of renal cell carcinoma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 33 publications
0
7
0
Order By: Relevance
“…In RCC, a number of miRNAs have identified associated with the prognosis of patients and functioned as prognostic biomarkers,23 such as miR-30a24 and miR-660-5p 25. A recent study demonstrated that the upregulation of miR-142-3p is correlated with poor prognosis of RCC patients and may be a prognostic biomarker 26. Therefore, investigation of cancer-associated miRNAs that are crucial for the progression of RCC may provide more therapeutic targets and prognosis improvement for RCC patients.…”
Section: Discussionmentioning
confidence: 99%
“…In RCC, a number of miRNAs have identified associated with the prognosis of patients and functioned as prognostic biomarkers,23 such as miR-30a24 and miR-660-5p 25. A recent study demonstrated that the upregulation of miR-142-3p is correlated with poor prognosis of RCC patients and may be a prognostic biomarker 26. Therefore, investigation of cancer-associated miRNAs that are crucial for the progression of RCC may provide more therapeutic targets and prognosis improvement for RCC patients.…”
Section: Discussionmentioning
confidence: 99%
“…Chen et al reported that miR-30a-3p could inhibit the invasion of RCC and serve as a new prognostic marker (21). miR-142-3p has also proved to be involved with tumorigenesis and the development of RCC (22). In addition to miRNAs, mRNAs including HHLA2 and syntaxin 6 were associated with decreased survival, and corresponding inhibitors held promise as a novel therapy against RCC (23,24).…”
Section: Discussionmentioning
confidence: 99%
“…miR-1181 was considered to be able to predict the prognosis of NSCLC, as its upregulation was associated with a poorer survival rate of patients with NSCLC. Accumulating evidence has demonstrated the prognostic value of miRNAs in several cancer types (26)(27)(28), and a variety of miRNAs, such as miR-519a, miR-378 and miR-1246, have been considered as prognostic biomarkers for NSCLC (29)(30)(31). In the present study, the results of the Cox regression analysis indicated that miR-1181 and the TNM stage were independent prognostic indicators for NSCLC.…”
Section: Discussionmentioning
confidence: 99%